Erector spinae plane block versus caudal epidural block in pediatric surgery: a systematic review and meta-analysis of randomized clinical trials - Barbara Bombassaro Masiero; Deivyd Cavalcante; Fatemeh Akbarpoor; Capela António Dicazeco Pascoal; Lubna Al-Sharif; Fellipe Feijó Halfeld; Lucas Cael Azevedo Ramos Bendaham; Patricia Viana; Jesslyn N. Haryianto; Maria Luiza de Souza Rasia; Mariana Copetti de Almeida Cunha; Ana Djulia Tesche; et al. (Brazilian Journal of Anesthesiology)
Background: Caudal Epidural Block (CEB) is a well-established regional anesthesia technique for abdominal and sub-abdominal pediatric surgeries. However, it has a short duration, often leading to additional analgesic administration. Erector Spinae Plane Block (ESPB), for instance, is an emerging technique that, like CEB, provides analgesic effect to a specific dermatome of the body during surgery and in the postoperative period. Therefore, we performed this systematic review with meta-analysis to compare both techniques. Methods: We searched PubMed, Embase and Cochrane Central for Randomized Controlled Trials (RCTs) comparing ESPB versus CEB in pediatric patients undergoing abdominal and sub-abdominal surgeries. The primary outcome was the time to first analgesic request. Secondary outcomes were I) FLACC score; II) Postoperative nausea and vomiting, and III) Urinary retention. Results: Nine randomized controlled trials encompassing 507 patients were included in this analysis (1‒9). The patients were predominantly male and under 10 years of age. There was an equal distribution between the two groups regarding the number of patients and patients’ baseline characteristics. The main results were: time to first analgesic request (MD = 3.71; 95% CI: -1.88–9.29; I2 = 99%; p = 0.19); FLACC scores at 2 hours (MD = 0.15; 95% CI: -0.30–0.59; I2 = 0%; p = 0.52); FLACC scores at 24 hours (MD = -0.17; 95% CI: -0.39–0.05; I2 = 41%; I2 = 41%; p = 0.13); urinary retention events (RR = 0.12; 95% CI: 0.02–0.94; I2 = 0%; p = 0.04); and Postoperative Nausea and Vomiting (PONV) which was null in both groups in three studies. However, it is important to clarify that some limitations were identified, such as significant heterogeneity in the following outcomes: time to first analgesic request and FLACC score at 24h, possibly due to different age groups, different types of surgeries, different background analgesia administration, and a relatively small sample size. As for the risk of bias, two studies were found to have some concerns in “bias due to deviations from intended interventions” (8,9). Conclusion: Our findings suggest that the administration of ESPB did not statistically differ from CEB regarding the time to first analgesic request. FLACC scores also did not show a statistically significant difference between groups. The ESPB group, however, experienced minor urinary retention events compared to the CEB group. Quality of evidence: According to the GRADE assessment, all outcomes evaluated in this study were classified as high-quality evidence. Quality assessment is detailed in Supplementary Table 1.